Role panchayat bodies in rural development: How to improve the functioning of panchayat institutions - Usha, K. (2012)
The socio-political changes expected from the introduction of panchayati raj system remained largely unfulfilled for long. Particularly the objectives like social equality, gender equity and changes at the grassroots level leadership envisaged as the main objectives of panchayati raj are not achieved in a meaningful manner. There is a need to change the system of planning at the all India level. A gradual shift from sectoral planning of area planning appears necessary in the context of people's participation in the planning process. The panchayats must also be given specific powers to pool resources and undertake integrated local development. - Reproduced.
Keywords: Panchayat